IMPLEMENTASI PENDIDIKAN KEPERCAYAAN TERHADAP TUHAN YANG MAHA ESA BAGI PESERTA DIDIK PENGANUT PENGHAYAT KEPERCAYAAN DI KABUPATEN GUNUNGKIDUL - Novianto, Victor; Indrianingrum, Nurullaila (Program Magister Pendidikan IPS UPY, 2024)
This study aims to determine: 1) The condition of education services for belief in God Almighty in Gunungkidul Regency; 2) Implementation of Trust Education in Gunungkidul Regency; 3) The driving and inhibiting factors for the implementation of education in belief in God Almighty for the community of believers in Gunungkidul Regency.This research is a descriptive research with a qualitative approach. The process of data collection was carried out by means of observation, interviews, and documentation. In analyzing the data, the researcher used qualitative analysis techniques with steps of data exposure, data reduction and drawing conclusions. The data validity technique used was data triangulation technique by checking the data from observations with interviews from research subjects with documentation. The results showed that; 1) the conditions for fulfilling the right to trust education for students who believe in faith in Gunungkidul Regency have not been fulfilled and are maximally supported by both the local government and the school; 2) of the 108 students who are registered as believers, there are only 4 students who have their faith education served at school; 3) the driving factor is the material basis, the inhibiting factor is communication, human resources, and disposition or attitudes.